Neuroprotective synergy of vitamin D and exercise: a narrative review of preclinical and clinical evidence on aging-related neuroplasticity and cognitive health - Chen, Jingfeng; Li, Yang; Wang, Li; Liu, Qi; Qiu, Bopeng (Frontiers in Nutrition, 2025)
BackgroundBoth vitamin D and physical exercise have been independently associated with neuroprotective and anti-aging effects. However, their potential synergistic role in promoting healthy brain aging has not been fully clarified.ObjectiveThis review examines the overlapping and potentially complementary effects of exercise and vitamin D on aging-related neurobiological and cognitive outcomes, with a focus on mechanisms relevant to older adults.MethodsWe surveyed preclinical and clinical studies investigating the impact of vitamin D and exercise on neurotrophic signaling (e.g., BDNF, IGF-1), vascular and inflammatory pathways (e.g., VEGF, cytokines), and cognitive or functional outcomes in aging models and older human populations. Particular attention was given to recent randomized controlled trials (RCTs) such as SYNERGIC, DO-HEALTH, and PONDER, as well as large-scale epidemiological studies.ResultsPreclinical findings suggest that vitamin D and exercise converge on shared biological pathways, including oxidative stress reduction, inflammation control, and neurogenesis promotion. Some animal studies demonstrated enhanced neuroprotection and cognitive improvement with combined interventions. In human trials, aerobic-resistance exercise with or without cognitive training improved cognitive scores in older adults with mild cognitive impairment, while vitamin D supplementation alone showed limited effect. Observational data further suggest that high serum vitamin D levels and regular physical activity are independently and jointly associated with delayed biological aging. However, evidence of clinically meaningful synergy remains limited, and no definitive conclusion can be drawn from current trials due to heterogeneity in design, population, and intervention protocols.ConclusionWhile biologically plausible and supported by selective findings, the synergistic impact of vitamin D and exercise on brain aging has yet to be conclusively demonstrated in older adults. Future studies should focus on at-risk populations, standardized intervention models, and mechanistic outcomes to better evaluate their combined potential as low-cost, preventive strategies in aging.